Respiratory restriction and elevated pleural and esophageal pressures in morbid obesity - Behazin, Negin; Jones, Stephanie B; Cohen, Robert I; Loring, Stephen H (Journal of applied physiology (1985), 2010)
Department of Anesthesia, Critical Care and Pain Medicine, Beth Israel Deaconess Medical Center, Boston, Massachusetts Submitted 10 October 2008 ; accepted in final form 11 November 2009 To explore mechanisms of restrictive respiratory physiology and high pleural pressure (P Pl ) in severe obesity, we studied 51 obese subjects (body mass index = 38–80.7 kg/m 2 ) and 10 nonobese subjects, both groups without lung disease, anesthetized, and paralyzed for surgery. We measured esophageal and gastric pressures (P Es , P Ga ) using a balloon-catheter, airway pressure (P AO ), flow, and volume. We compared P Es to another estimate of P Pl based on P AO and flow. Reasoning that the lungs would not inflate until P AO exceeded alveolar and pleural pressures (P AO > P Alv > P Pl ), we disconnected subjects from the ventilator for 10–15 s to allow them to reach relaxation volume (V Rel ) and then slowly raised P AO until lung volume increased by 10 ml, indicating the "threshold P AO " (P AO-Thr ) for inflation, which we took to be an estimate of the lowest P Alv or P Pl to be found in the chest at V Rel . P AO-Thr ranged from 0.6 to 14.0 cmH 2 O in obese and 0.2 to 0.9 cmH 2 O in control subjects. P Es at V Rel was higher in obese than control subjects (12.5 ± 3.9 vs. 6.9 ± 3.1 cmH 2 O, means ± SD; P = 0.0002) and correlated with P AO-Thr ( R 2 = 0.16, P = 0.0015). Respiratory system compliance (C RS ) was lower in obese than control (0.032 ± 0.008 vs. 0.053 ± 0.007 l/cmH 2 O) due principally to lower lung compliance (0.043 ± 0.016 vs. 0.084 ± 0.029 l/cmH 2 O) rather than chest wall compliance (obese 0.195 ± 0.109, control 0.223 ± 0.132 l/cmH 2 O). We conclude that many severely obese supine subjects at relaxation volume have positive P pl throughout the chest. High P Es suggests high P Pl in such individuals. Lung and respiratory system compliances are low because of breathing at abnormally low lung volumes. esophageal pressure; compliance; elastance; gastric pressure; pressure-volume curve Address for reprint requests and other correspondence: S. H. Loring, Dept. of Anesthesia, Critical Care and Pain Medicine, Dana 715, Beth Israel Deaconess Medical Center, 330 Brookline Ave., Boston, MA 02215 (e-mail sloringatbidmc.harvard.edu ).